Students Pronounciation Error Made in Speaking for General Communication - Maria Ramasari (Linguistic, English Education and Art (LEEA) Journal, 2017)
This qualitative research described students pronunciation error mostly appeared in speaking for general communication class. The participants were the first semester students. This research was descriptive method. It involved describing, analyzing, and interpreting of condition that existed. In collecting the data, the researcher used documentation. Based on the result of data analysis, it could be concluded that students made of three types of pronunciation error. The pronunciation errors were pre systematic error, systematic error, and post systematic error. Furthermore, the students dominant error made was pre systematic error. The errors of students made were caused by three sources of students competence error in learning English as Foreign Language. They were interference error, intra lingual error, and developmental error. Key words: pronunciation, error, speaking for general communication.